Unearthing business requirements : elicitation tools and techniques - Hossenlopp, Rosemary, 1958-; Hass, Kathleen B. (Vienna, VA : Management Concepts, 2008)
Helps learn how the business analyst works collaboratively with the project manager and other core team members to create plans that customize elicitation activities to the unique needs of the project. Presents techniques used by successful business analysts and defines key business analysis terms.
Includes index.
oif 22/06/15
Loan
Keywords: Business planning; Strategic planning; Project management